INNOVATIVE ASSETS IN THE ACCOUNTING AND NATIONAL ACCOUNTING - Galina Vasil’evna Mihaylova; Alexander Stepanovich Pavlov (Вестник Северо-Кавказского федерального университета, 2022)
In this article the problematic aspects of the reference reflection innovative assets. Special attention is paid to issues of intellectual property, which is the basis of capitalization and competitive advantages of the business. The role of professional judgment in assessing accounting and registration of innovations.